Foreign policy - Hossain, Ishtiaq (Cengage Learning Asia, 2013)
This chapter provides a broad view of Malaysia's foreign policy. It applies the "funnel of causality" to explain the various factors that shape the foreign policy of Malaysia. This is followed by an analysis of the aims and objectives of Malaysia's foreign policy. Finally, it provides a survey of foreign policy of Malaysia under the leadership of Prime Ministers Tunku Abdul Rahman, Tun Abdul razak bin Hussein, Tun Hussein Onn, Tun Dr. Mahathir Mohamad, Tun Abdullah bin Haji Ahmed Badawi, and Mohd Najib Tun Abdul Razak.